Occupational Safety And Health Risk Analysis (K3) Using The HIRADC Method On Cleaning service Workers In The Health Segment - Damayanti, Silvianah; Alifin, Fakhri Ikhwanul (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2024)
The healthcare industry is one of the industries that has a high risk of accidents and disease infection. Thus, the workers in this segment are vulnerable and require strict work rules to avoid the risks. The purpose of this study is to provide recommendations for preventive measures to reduce the risks faced by cleaning service workers in the health sector. Furthermore, the object of this study is an outsourcing company that provides cleaning service workers for several hospitals or healthcare institutions. The focus of this study includes i) identifying potential hazards, ii) risk assessments, and iii) risk control recommendations by using the HIRADC (Hazard Identification Risk Assessment and Determining Control) method. This study utilized primary information obtained through observation and interviews with the company's HSE (Health, Safety, and Environment) and samples from cleaning service workers in Indonesia. According to the results, the study found 15 medium risks and 19 low risks. Since several work accidents occurred to the cleaning services workers, it is still important to carry out appropriate risk control in the form of preventive measures to reduce the risks faced by workers, despite the medium and low-risk levels found in the company.